1978
DOI: 10.1021/j100515a020
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent conformation and vibrational spectra of 1,3-disilacyclobutane

Abstract: A detailed analysis of the vibrational spectra of 1,3-disilacyclobutane and 1,3-disilacyclobutane-l,1,3,3-d4 in vapor, liquid, and solid phases shows that the molecules have puckered ring conformations in the former two phases but become planar in the solid state. This is reflected by the frequency shifts of the ring deformation and SiH2 (or SiD2) rocking modes which are uncoupled for the planar conformation but interact strongly for the puckered structure. Frequency differences between gas and solid phases fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…For the characterization of organosilanes it is important to know the vibrational frequencies expected for the six modes associated with each SiX 2 group. Table compares the data from the present work for the silacyclobutanes (SCB) to those of 1,3-disilacyclobutanes (DSCB) , and 3-silacyclopentene (3SCP) . As can be seen, the functional group frequency associated with each type of vibration is in a narrow range for the Si−H and Si−D stretches but covers a broader wavenumber range for the lower frequency vibrations.…”
Section: Vibrational Assignmentsmentioning
confidence: 83%
“…For the characterization of organosilanes it is important to know the vibrational frequencies expected for the six modes associated with each SiX 2 group. Table compares the data from the present work for the silacyclobutanes (SCB) to those of 1,3-disilacyclobutanes (DSCB) , and 3-silacyclopentene (3SCP) . As can be seen, the functional group frequency associated with each type of vibration is in a narrow range for the Si−H and Si−D stretches but covers a broader wavenumber range for the lower frequency vibrations.…”
Section: Vibrational Assignmentsmentioning
confidence: 83%
“…Mixtures of the un-cross-linked and cross-linked forms of polymer 5a were prepared in Nujol and were used for IR analysis. The IR spectra showed that the intensity of the sharp peak at 930 cm -1 , which was assigned to the wagging mode of the CH 2 on the DSCB rings, decreased gradually as the curing reaction proceeded and that a broad peak is formed at 1050 cm -1 , which is assigned to the stretching mode for the bridging CH 2 group in the SiCH 2 Si open-chain structure (Figure ). ,,
5 IR spectra of polymer 5a in Nujol: (A) uncured, (B) cured at 220 °C for 2 h, (C) cured at 240 °C for 4 h, and (D) cured at 280 °C for 8 h.
…”
Section: Resultsmentioning
confidence: 99%
“…The additional strain imposed on the five-membered ring by substitution of CH2 by C=0 favors the planar ring in this case and 0 is reduced. The epimers thujone and isothujone, both of which are bicyclic monoterpenes derived from 98 by substituting isopropyl and methyl at the 1 and 4 positions, respectively, have been shown418 to have ring conformations similar to that of 98. On the other hand, when a double bond is placed in the five-membered ring of 93 to give bicyclo[3.1.0]hex-2-ene (99), the two endocyclic trigonal carbon atoms now hold the ring essentially planar417 (see Table XVIII).…”
Section: Bicyclic Compounds Containing Five-membered Ringsmentioning
confidence: 99%